Load Tooth Contact Analysis for Arc Tooth Face Gear Considering Assembly Misalignment - Cui Yanmei; Fang Zongde; Wang Xing (Jixie chuandong)
The generating method is adopted for processing arc tooth face gear to ensure the meshing precision of arc tooth face gear pair. The tooth face contact model is established with assembly misalignment. By application of the elastic contact mechanics,finite element influence matrix method and mathematical programming method,the load tooth contact analysis for arc tooth face gear is carried out,the load distribution and contact stress of tooth surface pair are studied in different installation error. Compared to the spur tooth face gear pair,the arc tooth face gear pair has the big overlap ratio,the small contact stress,the stability of transmission,the high loading capacity,and the small sensitivity toward installation error. The method for the tooth face gear pair provides systematic theoretical direction such as the design,the experiment and the application.